Causes and effects of rural-urban migration in Nepal: Case of Dev Community in Biratnagar - Chaudhary, Sandip (Journey for Sustainable Development and Peace Journal, 2025)
The study aims to analyze the reasons behind the migration from rural areas of the Saptari district to Biratnagar Metropolitan City, Koshi Province of Nepal, as well as to examine the changes in their socioeconomic status among the Dev community. It explores the influences of migration in occupation, income, lifestyle, land ownership, and other socioeconomic factors among the members of the Dev community in Biratnagar, using a qualitative approach. A total of thirty-three household respondents were purposively selected and interviewed using a semi-structured questionnaire and checklist. The data gathered from primary sources in the field reveal significant changes in socioeconomic fields compared to the past. Traditionally, the Dev community engaged in agriculture and livestock; however, currently, very few members are involved in agriculture even in their native places. Instead, most have transitioned to the service sector, with only a small number participating in business activities. The primary motivations driving rural-urban migration include the search for employment opportunities and quality of livelihood.